Dietary status of exclusively breastfeeding mothers: The Influence of traditional postpartum dietary practices - Abdul Basir, Siti Munirah; Abdul Ghani, Radiah; Ibrahim, Muhammad; Khattak, Muhammad Muzaffar Ali Khan; Omar, Muhammad Nor; Mohd Shukri, Nor Azwani (IIUM Press, 2019)
Human milk is recognized as the normative standard for infant feeding (Moretti, 2012; WHO, 2011). It is a unique food that contains both nutrients and non-nutritive bio-active factors suited to human infants. The World Health Organization (WHO) and United Nations Children’s Fund (UNICEF) strongly advocate exclusive breastfeeding for the first six months after birth as the optimal way of feeding infants based on evidence which showed beneficial effects on child health, growth and development as well as positive implications on maternal wellbeing (WHO, 2009; UNICEF, 2016). The Malaysian government has consequently adopted this recommendation in its Malaysian Dietary Guidelines (MDG) which encourage mothers to practise breastfeeding from birth until six months and continue to breastfeed for two years (Key Message 1, MDG, 2013). The aim of this review was to discuss the potential influence of traditional postpartum dietary practices on maternal dietary status during exclusive breastfeeding period. Besides duration, the nutritional quality of human milk is also an important aspect of breastfeeding. One of the factors that may influence this is the maternal diet.Lactation comes with a higher nutritional demand and greater than that of pregnancy. Thus, there is a need to optimize maternal food intake during lactation period in order to meet the elevated energy and micronutrients requirements. However, among Asian populations, maternal nutritional intake during this crucial period may be affected by the common traditional postpartum practices which involve dietary restrictions and prohibitions. These practices, however, may impact mothers’ ability to meet the increased energy and nutrients needs during breastfeeding period. Inadequate dietary intake during lactation may compromise the nutritional status of the mother, her recovery back to health, and her human milk production. Consequently, inadequate amounts of human milk may pose malnutrition risk for the infant. Thus, it is crucial for the mother to maintain good nutritional intake especially during the confinement period in order to ensure optimal recovery, breastfeeding success, and satisfactory nutritional status of her baby.